2014
DOI: 10.11648/j.ijsedu.20140205.11
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention on Verbal Violence among Students with Intellectual Disabilities

Abstract: This article focus on verbal violence among students with intellectual disabilities (ID). The purpose of the research was to assess the impact of an intervention program based on the model of the "Cycle of Internalized Learning" (Reiter, 2008), on the reduction of verbal violence and to find out if there are gander differences in the use of verbal violence. The sample consisted of 44 students with ID attending 5 classrooms. Three classrooms were the experimental group (N = 20) and two classes were the comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The researchers both had extensive experience in working with adults with disabilities. One had focused their research on verbal violence toward adults with disabilities and had previously used the CIL model in studies with children with IDD (Karni, 2014). The second researcher had engaged primarily in qualitative research of strategies to support adults with disabilities (Neuman, 2020a(Neuman, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers both had extensive experience in working with adults with disabilities. One had focused their research on verbal violence toward adults with disabilities and had previously used the CIL model in studies with children with IDD (Karni, 2014). The second researcher had engaged primarily in qualitative research of strategies to support adults with disabilities (Neuman, 2020a(Neuman, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such violence is often perpetrated by familiar people, caregivers, relatives, friends, and professionals (McGowan & Elliott, 2019; Scolese et al, 2020). Research has shown that people with IDD are exposed to violence 10 times more than people without disabilities (Dembo et al, 2018; Karni, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation